2021
DOI: 10.1007/s11947-021-02742-8
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Ultraviolet Light–Emitting Diode Technology in Horticultural Produce: a Systematic Review and Meta-analysis

Abstract: Essential factor influencing the growth of plants is quality and type of light, development, and accumulation of phytochemicals, especially those grown in controlled conditions. Light is essential source for photosynthesis in higher plants, whereas light signalling is important in plant morphogenesis. The development of LED technologies enables for the optimization of photosynthetic processes and the regulation of plant physiology through the manipulation of light parameters. The plant morphology and functioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…It was reported that supplemental UV-A light resulted in bigger biomass, leaf area, pigment, antioxidant, and aliphatic glucosinolate contents in Chinese kale [17][18][19]; higher shoot biomass, antioxidant phenolics and sugar alcohols in ice plants [20]; higher biomass [21], anthocyanin and ascorbic acid [21], as well as increased protein concentration, mineral nutrients [22] in lettuce. Though showing comparable general trends, studies report species, UV-A dosage, and UV-A wavelengthspecific impacts [23][24][25][26]. Differential experimental conditions and basic lighting properties aggravate the comparison of the results.…”
Section: Introductionmentioning
confidence: 92%
“…It was reported that supplemental UV-A light resulted in bigger biomass, leaf area, pigment, antioxidant, and aliphatic glucosinolate contents in Chinese kale [17][18][19]; higher shoot biomass, antioxidant phenolics and sugar alcohols in ice plants [20]; higher biomass [21], anthocyanin and ascorbic acid [21], as well as increased protein concentration, mineral nutrients [22] in lettuce. Though showing comparable general trends, studies report species, UV-A dosage, and UV-A wavelengthspecific impacts [23][24][25][26]. Differential experimental conditions and basic lighting properties aggravate the comparison of the results.…”
Section: Introductionmentioning
confidence: 92%
“…LEDs are more energy-efficient and environmentally friendly than most traditional light sources used in horticulture (e.g. high-pressure sodium vapour or metal halide lamps), and by utilising LEDs that emit both in the UV and PAR regions the control of the spectral composition, intensity and exposure period can be attuned to the light requirements of specific plants and crops [ 373 , 374 ]. However, at present, only UV-A LEDs have been widely adopted to stimulate the accumulation of desirable plant compounds [ 375 ].…”
Section: Effects On Agriculture and Food Productionmentioning
confidence: 99%
“…Ultraviolet light emitting diodes in the food industry are used in three main areas: food production, post-harvest storage, and food safety ( 17 , 18 ). Furthermore, this technology is one of the most promising alternatives for extending the shelf life of fruits and vegetables ( 56 ). Studies have been published showing the efficiency of LEDs in post-harvest applications, where LEDs were able to accelerate secondary metabolites during the ripening process ( 57 ), and both increase the volume and delay the loss of nutritional content in fruits and vegetables such as broccoli, citrus fruits, and strawberries ( 57 59 ).…”
Section: Applicationsmentioning
confidence: 99%